Marketing of shrimp in Bangladesh-A value chain analysis (Journal of the Bangladesh Agricultural University, 2016)
Shrimp is an important fisheries resource in the national economy of Bangladesh. It is considered as an exportable item and in each year it shared about 2.75% of the total export earning of Bangladesh. The present study was conducted to examine the marketing system and value chain, and marketing efficiency of shrimp marketed both in domestic and export market. For this study a total of 182 stakeholders (market intermediaries) were selected where shrimp farmers, export oriented farms, depot owners and other market participants and selling agents were included. Data were collected for the period of 2012-13. The study revealed that 80% shrimp is exported and rest 20% is consumed in the local market. Usually shrimp is exported through exporting agencies and firms. Considering all kinds of market, the average gross marketing margin and profit of shrimp in the local market were Tk 171.00/kg and Tk 134.04/kg respectively but for export market, the corresponding amounts were Tk 142.76/kg and Tk 89.51/kg respectively. Shrimp is sold both in domestic and overseas market and accordingly major supply chain and value chain were identified. Shrimp farmers and exporting agencies supply shrimp to ultimate consumers through supply chain. Actually value chain actors added value at each level of market. After processing and adding value, domestic and overseas consumers purchase 1 kg of shrimp at Tk 55.00 and Tk 142.76 respectively. Marketing efficiency was studied only for domestic market. It revealed that shorter supply channel resulted efficient marketing of shrimp where the shrimp producer received the higher percentages of sales price provided by the retailer in consumer market.J. Bangladesh Agril. Univ. 12(2): 359-368, December 2014